2014
DOI: 10.1097/qad.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Predicting treatment failure in adults and children on antiretroviral therapy

Abstract: The 2010 WHO clinical and immunologic criteria are insensitive and have low PPV for predicting virologic failure. These data support the strong recommendation 2013 treatment guidelines that viral load testing be used to monitor for, diagnose, and confirm ART failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 39 publications
2
42
2
1
Order By: Relevance
“…The clinical algorithms constructed in Sub-Saharan Africa (2 in Uganda and 1 in South Africa), had sensitivities ranging from 67% to76% [1517], external validations of these algorithms are yet to be published. The sensitivity of the 2013 WHO criteria was higher in this cohort (67%) compared with previously reported data [15,16,18]. For targeting viral load testing, however, misclassification of 33% of subjects with VF cannot be accepted.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The clinical algorithms constructed in Sub-Saharan Africa (2 in Uganda and 1 in South Africa), had sensitivities ranging from 67% to76% [1517], external validations of these algorithms are yet to be published. The sensitivity of the 2013 WHO criteria was higher in this cohort (67%) compared with previously reported data [15,16,18]. For targeting viral load testing, however, misclassification of 33% of subjects with VF cannot be accepted.…”
Section: Discussioncontrasting
confidence: 62%
“…However, these criteria are not evidence-based, and have poor performance [18]. Alternative strategies for detection of treatment failure are therefore required for ART programs in low-income countries until universal VL monitoring is established.…”
Section: Introductionmentioning
confidence: 99%
“…WHO recommends VL testing as the preferred monitoring approach to diagnose and confirm treatment failure [2]. A systematic review found that current WHO clinical and immunological criteria have low sensitivity and low positive predictive value for identifying individuals with virological failure [24]; however, an evaluation from resource-limited countries found no evidence of improved mortality, reduced clinical failure or loss of treatment options when compared to programmes with VL testing [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…6 Many rural clinics in sub-Saharan Africa therefore opt for WHO clinical staging and the widely available immunological monitoring based on CD4 cell measurement to monitor response to ART, 5,7,8 despite immunological monitoring being an imperfect way to identify treatment failure. 9 …”
Section: Introductionmentioning
confidence: 99%